Chemical Modification of Oleic Acid Derived Palm Oil as Chemical Processor for Polyols Production - Ismail Md Rasib; Mohd Zulkpli Ab Kadir; Intan Suhada Azmi; Mohammad'Aathif Addli; Noorfazlida Mohamed; Mohamad Zarqani Yeop; Mohd Azril Riduan; Mohd Jumain Jalil (Chemical Engineering Transactions, 2023)
In recent years, research on the epoxidation of fatty acids has attracted considerable attention due to the growing demand for eco-friendly epoxides generated from vegetable oils. Commercially available epoxides are primarily derived from petroleum and animal fats, which are non-environmentally friendly sources. Epoxide is a crucial chemical precursor for the manufacture of alcohols, glycols, and polymers such as polyesters and epoxy resin. The optimal process parameters were determined using the one factor at a time (OFAT) technique. This study's purpose is to identify the optimal process parameter for agitation speed in relation to the oxirane ring opening of epoxidized oleic acid. The result at 100 rpm and sulfuric acid as catalyst are the optimal process setting for achieving maximal relative oxirane conversion (93 %). Then, the ring opening formation's identity was validated using Fourier Transform Infrared (FTIR).